Fabrication of Bi0.5Na0.5ZrO3 powder by mixed oxide method - Jaiban P. (2014)
Lead-free bismuth sodium zirconate powder with formula Bi 0.5Na0.5ZrO3 was prepared by conventional mixed oxide method. Bismuth sodium zirconate (BNZ) powder with 10wt%Na 2CO3 was calcined at 800 °C for 2 h dwell time. Investigation of the effects of recalcination and dwell time on phase formation of powders was also carried out. The results revealed that re-calcination significantly affected the formation of single-phase BNZ powder. Phase characteristics were checked by X-ray diffraction (XRD). Powder Cell software was employed to simulate crystal structure of BNZ powder. It was found that BNZ powder most likely possessed an orthorhombic structure. SEM result showed its average particle size was 0.47 μm and composition measured EDX correlated with theoretical composition of BNZ. © (2011) Trans Tech Publications.